Aspects of feminine mythology and related pictoral imagery as source for the development of a personal sculptural iconography - Norman, Lee (Michaelis School of Fine Art, 2023)
The representation of the female figure in Western society has been moulded by such diverse forces as religion, economy and geography, nonetheless, certain images of the female form and representations of feminine qualities appear to be archetypal. One example is that of the Venus of Willendorf which has been recognised as a generalised image of women's fertility. This is mainly due to its formal exaggeration of, and emphasis on, the reproductive aspects of women's bodies. A second example is contained in the theories of Jungian psychologists who have recognised the feminine principle as embodied in the myths and pictorial imagery of what is known as the great goddess. They maintain that the symbols and images from these myths are similar to those in the myths, dreams and fantasies of modern individuals. Following on from these insights the first series of sculptures was aimed at examining women's experience of the reproductive aspects of their bodies in patriarchal society. Generalised images of female fertility were represented through the expressive device of exaggeration. I was concerned to express each woman's individuality by including facial details and gesture. It was also necessary to depict conventionalised elements of patriarchal society. This was achieved through a personification of bestial attributes. The ceramic medium offered many advantages, among them, its primordial qualities and its suitability for modelling and casting voluminous forms. An interest in broader aspects of femininity developed out of the study of images of the great goddess. This was facilitated by a reading of Jungian contrasexual psychology which maintains that the feminine principle is a universal psychological element specific to both men and women. The intention in the second series of sculptures was to celebrate this principle. Since it is not gender-related, it was necessary to find imagery other than that of the female figure. The feminine principle is not definable in purely physical terms since it is experienced in the conscious and unconscious mind, in fantasy, and in what is taken for reality. Abstract symbols associated with goddess mythology were recontextualised in this series and were intended to function on several layers of perception. The technique of modelling cement onto a metal armature facilitated the bold and celebratory forms chosen to celebrate the feminine principle.